Positive electrode electrolyte of redox flow battery, preparation method of positive electrode electrolyte and redox flow battery

By introducing soluble Prussian blue derivatives and polyvinylpyrrolidone as composite additives into the positive electrode electrolyte of the flow battery, the problems of low solubility and instability of ferrocyanide salt are solved, and a flow battery with high energy density and long-term circulation stability are achieved.

CN119905623APending Publication Date: 2025-04-29CHANGSHA HECHU NEW MATERIAL TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411871336.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The low solubility of ferrocyanide salt limits the unit volume capacity and energy density of the flow battery, and there are problems of instability and low ion conduction under high solubility.

Method used

Compound additives, including soluble Prussian blue derivatives and polyvinylpyrrolidone, are introduced into the positive electrode electrolyte of the liquid flow battery, to weaken the hydrogen bonding, increase the entropy and disorder of the electrolyte, thereby improving battery performance.

Benefits of technology

It significantly improves the energy density and long-term circulation stability of the flow battery, enhances the ion conduction ability of the electrolyte, and realizes a high entropy, high capacity and long-life sulfhydryl fluid flow battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905623A_ABST
    Figure CN119905623A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of flow batteries, and provides a flow battery positive electrode electrolyte, a preparation method thereof and a flow battery. The positive electrode electrolyte comprises the following components: ammonium ferrocyanide, lithium ferrocyanide, a composite additive and a supporting electrolyte; the composite additive comprises a soluble Prussian blue derivative and / or polyvinylpyrrolidone. The concentration of an iron active substance on the positive electrode side is greatly increased by using two or more ferrocyanide as the sulfur-iron flow battery positive electrode electrolyte, and the soluble Prussian blue derivative and polyvinylpyrrolidone are used as the composite additive, so that on one hand, the hydrogen-bond interaction of mixed salt and water can be weakened, water clusters are reduced, and on the other hand, the concentration of the iron active substance on the positive electrode side can be reduced; on the other hand, the interaction of anions and cations in the electrolyte can be weakened, so that a large-scale structure cluster is destroyed, and the performance and long-term cycling stability of the battery are jointly improved through the mutual cooperation of the anions and cations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of liquid flow batteries, and in particular relates to a positive electrode electrolyte for a liquid flow battery and a preparation method thereof, and a liquid flow battery. Background Art

[0002] In recent years, people's demand for renewable clean energy has been increasing, and the efficient use of renewable energy has become a topic of great concern. However, renewable energy is still facing the problem of unsustainable and unstable output. Therefore, it is urgent to develop large-scale and effective energy storage technology to supplement the shortcomings of renewable energy utilization.

[0003] Sulfur-iron flow batteries with ferrocyanide as the positive electrode and polysulfide as the negative electrode are expected to be gradually commercialized due to their cheap raw materials, non-toxicity and electrochemical reversibility. However, the low solubility of ferrocyanide limits its battery unit volume capacity and energy density, requiring a larger floor space and electrolyte cost, thus failing to meet the commercial application requirements of the system. Among ferrocyanide salts, lithium ferrocyanide and ammonium ferrocyanide have much higher solubility than other ferrocyanide salts (the solubility of ammonium ferrocyanide is 1.6 M, and the solubility of lithium ferrocyanide is 1.92 M) because their cations can produce hydrogen bonds with water molecules. The use of these two ferrocyanide salts can greatly improve the battery unit volume capacity and energy density, but they still have some problems. For example, ammonium ferrocyanide will reduce the pH of the electrolyte during long-term battery testing and cause safety problems; strong hydrogen bond interactions will cause water clusters in the electrolyte, which is easy to cause electrolyte crystallization at low temperatures; high solubility causes clustering between anions and cations in the electrolyte, making the electrolyte have lower ion conductivity, etc.

[0004] Therefore, the flow battery system with ferrocyanide as the positive electrode electrolyte still needs further improvement and development. Summary of the invention

[0005] The technical problem to be solved by the present invention is that the solubility of ferrocyanide is low, which limits its battery unit volume capacity and energy density, and the instability of ferrocyanide at high solubility and the low ion conductivity caused by ion clustering. The shortcomings and defects mentioned in the above background technology are overcome, and a liquid flow battery positive electrode electrolyte, a preparation method thereof, and a liquid flow battery are provided.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: A positive electrolyte for a liquid flow battery, the positive electrolyte comprising the following components: ferrocyanide, a composite additive and a supporting electrolyte, wherein the molar ratio of the composite additive to the ferrocyanide is 0.1-5%; The composite additive comprises a soluble Prussian blue derivative and / or polyvinyl pyrrolidine.

[0007] The present invention aims at a high-solubility, high-capacity liquid flow battery electrolyte. A composite additive is introduced into the mixed ferrocyanide to weaken hydrogen bonds, weaken the interaction between anions and cations in the electrolyte, increase the entropy of the electrolyte, and increase the disorder of the electrolyte microstructure to improve battery performance; the supporting electrolyte further enhances the conductivity of the electrolyte and adjusts the environmental pH so that the battery system is maintained in an alkaline environment, thereby improving stability, and ultimately successfully constructing a high-entropy, high-capacity, long-life ferric sulfide liquid flow battery.

[0008] The soluble Prussian blue derivative in the composite additive can make the ferrocyanide complex more stable at high concentrations, thereby enhancing the stability of the battery. On the one hand, polyvinyl pyrrolidone weakens the hydrogen bonding between the mixed ferrocyanide and water, reduces water clusters, and enhances the stability of the electrolyte. On the other hand, it can weaken the interaction between anions and cations in the electrolyte, thereby destroying large-scale structural clusters, making the electrolyte have disordered high entropy characteristics, and enhancing the ionic conductivity of the electrolyte. Moreover, when soluble Prussian blue is used alone, anions and cations in the solution will interact with each other, thereby causing large-scale clusters. When the two are used together in a certain proportion, the soluble Prussian blue derivative and polyvinyl pyrrolidone can make the ferrocyanide complex in the electrolyte more stable while weakening the large-scale clusters of anions and cations therein, thereby improving the ionic conductivity of the electrolyte, and jointly achieving long-term and efficient energy storage.

[0009] Preferably, the ferrocyanide comprises two or more species. Two or more ferrocyanides are selected to increase their upper solubility limit, and the total concentration of ferrocyanide is 1-3M.

[0010] Preferably, the ferrocyanide is ammonium ferrocyanide and lithium ferrocyanide, and the molar ratio of ammonium ferrocyanide to lithium ferrocyanide is 1:10-10:1. The cationic ammonium ions and lithium ions in ammonium ferrocyanide and lithium ferrocyanide can produce hydrogen bonds with water molecules, thereby greatly improving the solubility of the positive electrode and increasing the battery capacity.

[0011] Through this scheme, the iron in ferrocyanide exists in a complex with cyanide and will not react with the hydroxide in the supporting electrolyte; by combining two or more ferrocyanides to increase the solubility of iron in the positive electrolyte, the positive electrode active material of the sulfur-iron flow battery can be increased, greatly improving the capacity of the battery and reducing the volume of the electrolyte.

[0012] Preferably, the ratio of the amount of the soluble Prussian blue derivative to the amount of polyvinyl pyrrolidine is 1:3-3:1.

[0013] Preferably, the supporting electrolyte includes sodium hydroxide and / or potassium hydroxide, and the concentration of the supporting electrolyte is 0.1-2 M. Hydroxides can enhance the conductivity and charge transfer rate of the electrolyte.

[0014] Under the same technical concept, the present application also provides a method for preparing the positive electrolyte of the liquid flow battery, comprising the following steps: The supporting electrolyte, ferrocyanide and the composite additive are dissolved, stirred and mixed to form a mixed solution, wherein the concentration of the supporting electrolyte in the mixed solution is 0.1-2M.

[0015] Preferably, the ferrocyanide is dissolved at 50°C-80°C.

[0016] Under the same technical concept, the present application also provides a liquid flow battery, wherein the liquid flow battery is a sulfide-iron liquid flow battery, and the liquid flow battery comprises the liquid flow battery positive electrode electrolyte.

[0017] Preferably, the negative electrode electrolyte of the liquid flow battery is disodium tetrasulfide, the diaphragm is a cation exchange membrane, the positive electrode is blank carbon felt, and the negative electrode is carbon felt loaded with a catalyst.

[0018] Preferably, the flow battery is at 80 mA / cm -2 The energy efficiency reaches over 65% at a current density of 1.5 % and remains above 65% after 300 consecutive cycles. Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses ferrocyanide as the positive electrode electrolyte of the sulfur-iron flow battery, which greatly increases the concentration of the iron active material on the positive electrode side, significantly improves the energy density, and reduces the system cost; the ferrocyanide used in the present invention has high solubility, and the concentration of ferrocyanide in the positive electrode electrolyte of the flow battery can reach 2.3 M or above, thereby increasing the discharge capacity of the battery; (2) The present invention utilizes soluble Prussian blue and polyvinyl pyrrolidone as composite additives, which can weaken the hydrogen bonding between the mixed salt and water, reduce water clusters, and enhance the stability of the electrolyte on the one hand; on the other hand, they can weaken the interaction between anions and cations in the electrolyte, thereby destroying large-scale structural clusters, making the electrolyte have disordered high entropy characteristics, and enhancing the ionic conductivity of the electrolyte. The two work together to improve the performance of the battery and the long-term cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 It is a test diagram of energy efficiency performance under long-time constant current charge and discharge of Examples 1, 2, 3 of the present invention and Comparative Examples 1, 2, 3; Figure 2 The results of Example 1 and Comparative Examples 1, 2 and 3 at 80 mA / cm -2 Energy efficiency diagram for long-term cycling at different current densities; Figure 3 1 is a graph of coulombic and voltage efficiencies of Examples 1, 2, 3 of the present invention and Comparative Examples 1, 2, 3 at different current densities; Figure 4 This is a test diagram of energy efficiency performance under long-term constant current charge and discharge of Example 4 of the present invention; Figure 5 1 is a discharge capacity diagram of embodiments 1, 5 and 6 of the present invention; Figure 6 Graphs showing the coulombic efficiency and energy efficiency of Examples 5 and 6 of the present invention and Comparative Example 4. DETAILED DESCRIPTION

[0021] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0022] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0023] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0024] Example 1 A method for preparing a positive electrolyte for a liquid flow battery comprises the following steps: S1. Weigh 1 M equivalent of sodium hydroxide and dissolve it in water to form a mixed solution; S2, weighing a total of 2.3 M equivalents of a mixed salt of ammonium ferrocyanide and lithium ferrocyanide (a molar ratio of 1:1) and placing it in the mixed solution of step S1, stirring at 80° C. until dissolved, to obtain a mixed salt solution; the ammonium ferrocyanide and lithium ferrocyanide in the mixed salt solution are completely dissolved; S3. Weigh 10 mM equivalent of a composite additive (a soluble Prussian blue derivative (MnFe[Fe(CN)6xH2O]) and polyvinyl pyrrolidone in a molar ratio of 1:1) and place it in the mixed solution of step S2, stir and dissolve, and obtain a positive electrode electrolyte for a liquid flow battery.

[0025] The battery performance test of the prepared positive electrolyte of the flow battery is carried out: 1. The positive electrode electrolyte of the liquid flow battery is the electrolyte prepared in Example 1, the negative electrode electrolyte is a mixed solution of 1.7 M sodium tetrasulfide and 1 M sodium hydroxide, the diaphragm is Nafion, the positive electrode is blank carbon felt, and the negative electrode is carbon felt loaded with a catalyst.

[0026] 2. The performance test is carried out using the charge and discharge rate. The energy efficiency performance test results under long-term constant current charge and discharge are as follows: Figure 1 , at 80 mA / cm -2 The energy efficiency of long-term cycling at current density is shown in Figure 2. Figure 2 As shown, the discharge capacity diagram is as follows Figure 5 As shown, at 80 mA / cm -2 The coulomb efficiency is 99.5%, the voltage efficiency is 73.8%, and the energy efficiency is 73.5%.

[0027] 3. Stability is also an important indicator for measuring electrolyte. Long-term constant current charge and discharge test is used. The test results are as follows: Figure 3 As shown, at 80 mA / cm -2 After 300 consecutive cycles, the energy efficiency is 72.8%, with basically no attenuation.

[0028] Example 2 A method for preparing a positive electrolyte for a liquid flow battery comprises the following steps: S1. Weigh 1 M equivalent of sodium hydroxide and dissolve it in water to form a mixed solution; S2, weighing a total of 2.3 M equivalents of a mixed salt of ammonium ferrocyanide and lithium ferrocyanide (a molar ratio of 1:1) and placing it in the mixed solution of step S1, stirring at 80° C. until dissolved, to obtain a mixed salt solution; the ammonium ferrocyanide and lithium ferrocyanide in the mixed salt solution are completely dissolved; S3. Weigh 10 mM equivalent of additives (soluble Prussian blue derivative (MnFe[Fe(CN)6xH2O]) and polyvinyl pyrrolidone in a molar ratio of 1:3) and place it in the mixed solution of step S2, stir and dissolve to obtain a positive electrode electrolyte for a liquid flow battery.

[0029] The battery performance test was carried out on the prepared sulfur-iron liquid flow battery cathode electrolyte: 1. The positive electrode electrolyte of the liquid flow battery is the electrolyte prepared in Example 2, the negative electrode electrolyte is a mixed solution of 1.7 M sodium tetrasulfide and 1 M sodium hydroxide, the diaphragm is Nafion, the positive electrode is blank carbon felt, and the negative electrode is carbon felt loaded with catalyst.

[0030] 2. The performance test is carried out using the charge and discharge rate. The energy efficiency performance test results under long-term constant current charge and discharge are as follows: Figure 1 , at 80 mA / cm -2 The energy efficiency of long-term cycling at current density is shown in Figure 2. Figure 2 As shown, the Coulomb and voltage efficiency diagrams at different current densities are shown in Figure 3 As shown, the result is that at 80 mA / cm -2 The coulomb efficiency is 99.3%, the voltage efficiency is 70.35%, and the energy efficiency is 70.01%.

[0031] Example 3 A method for preparing a positive electrolyte for a liquid flow battery comprises the following steps: S1. Weigh 1 M equivalent of sodium hydroxide and dissolve it in water to form a mixed solution; S2, weighing a total of 2.3 M equivalents of a mixed salt of ammonium ferrocyanide and lithium ferrocyanide (a molar ratio of 1:1) and placing it in the mixed solution of step S1, stirring at 80° C. until dissolved, to obtain a mixed salt solution; the ammonium ferrocyanide and lithium ferrocyanide in the mixed salt solution are completely dissolved; S3. Weigh 10 mM equivalent of the composite additive (a soluble Prussian blue derivative (MnFe[Fe(CN)6xH2O]) and polyvinyl pyrrolidone in a molar ratio of 3:1) and place it in the mixed solution of step S2, stir and dissolve, and obtain a positive electrode electrolyte for a liquid flow battery.

[0032] The battery performance test was carried out on the prepared sulfur-iron liquid flow battery cathode electrolyte: 1. The positive electrode electrolyte of the liquid flow battery is the electrolyte prepared in Example 3, the negative electrode electrolyte is a mixed solution of 1.7 M sodium tetrasulfide and 1 M sodium hydroxide, the diaphragm is Nafion, the positive electrode is blank carbon felt, and the negative electrode is carbon felt loaded with catalyst.

[0033] 2. The performance test was carried out using the charge and discharge rate. The result was that at 80 mA / cm-2 The coulomb efficiency is 99.4%, the voltage efficiency is 68.99%, and the energy efficiency is 68.58%.

[0034] Example 4 A method for preparing a positive electrolyte for a liquid flow battery comprises the following steps: S1. Weigh 1 M equivalent of sodium hydroxide and dissolve it in water to form a mixed solution; S2, weighing 1.0 M equivalent of a mixed salt of sodium ferrocyanide and potassium ferrocyanide (a molar ratio of 1:1) and placing it in the mixed solution of step S1, stirring at 80° C. until dissolved, to obtain a mixed salt solution; the sodium ferrocyanide and potassium ferrocyanide in the mixed salt solution are completely dissolved; S3. Weigh 4.5 mM equivalent of a composite additive (a soluble Prussian blue derivative (MnFe[Fe(CN)6xH2O]) and polyvinyl pyrrolidone in a molar ratio of 1:1) and place it in the mixed solution of step S2, stir and dissolve, and obtain a positive electrode electrolyte for a liquid flow battery.

[0035] The battery performance test was carried out on the prepared sulfur-iron liquid flow battery cathode electrolyte: 1. The positive electrode electrolyte of the liquid flow battery is the electrolyte prepared in Example 4, the negative electrode electrolyte is a mixed solution of 0.75M disodium tetrasulfide and 1M sodium hydroxide, the diaphragm is Nafion, the positive electrode is blank carbon felt, and the negative electrode is carbon felt loaded with catalyst.

[0036] 2. Use the charge and discharge rate to perform performance testing, and the energy efficiency diagram is as follows Figure 4 As shown, the test results are, at 80 mA / cm -2 The coulomb efficiency is 99.25%, the voltage efficiency is 73.38%, and the energy efficiency is 72.83%.

[0037] It can be seen from Example 4 and Example 1 that the composite additive not only acts on ammonium ferrocyanide and lithium ferrocyanide, but also has the same effect on other ferrocyanides.

[0038] Example 5 A method for preparing a positive electrolyte for a liquid flow battery comprises the following steps: S1. Weigh 1 M equivalent of sodium hydroxide and dissolve it in water to form a mixed solution; S2, weighing 1.6 M equivalent of ammonium ferrocyanide and placing it in the mixed solution of step S1, stirring at 80° C. until dissolved, to obtain a mixed salt solution; S3. Weigh 7.2 mM equivalent of a composite additive (a soluble Prussian blue derivative (MnFe[Fe(CN)6xH2O]) and polyvinyl pyrrolidone in a molar ratio of 1:1) and place it in the mixed solution of step S2, stir and dissolve, and obtain a positive electrode electrolyte for a liquid flow battery.

[0039] The battery performance test was carried out on the prepared sulfur-iron liquid flow battery cathode electrolyte: 1. The positive electrolyte of the liquid flow battery is the electrolyte prepared in Example 5, the negative electrolyte is a mixed solution of 1.2 M sodium tetrasulfide and 1 M sodium hydroxide, the diaphragm is Nafion, the positive electrode is blank carbon felt, and the negative electrode is carbon felt loaded with catalyst.

[0040] 2. Use the charge and discharge rate to perform performance test, and the discharge capacity diagram is as follows: Figure 5 As shown, the coulombic efficiency, energy efficiency and voltage efficiency are Figure 6 As shown, the performance test results are: -2 The coulomb efficiency is 99.32%, the voltage efficiency is 73.48%, and the energy efficiency is 72.98%.

[0041] Example 6 A method for preparing a positive electrolyte for a liquid flow battery comprises the following steps: S1. Weigh 1 M equivalent of sodium hydroxide and dissolve it in water to form a mixed solution; S2, weighing 1.92 M equivalent of lithium ferrocyanide and placing it in the mixed solution of step S1, stirring at 80° C. until dissolved, to obtain a mixed salt solution; S3, weigh 8.64 mM equivalent of the composite additive (a soluble Prussian blue derivative (MnFe[Fe(CN)6xH2O]) and polyvinyl pyrrolidone in a molar ratio of 1:1) and place it in the mixed solution of step S2, stir and dissolve to obtain a positive electrode electrolyte for a liquid flow battery; perform a battery performance test on the prepared sulfur iron liquid flow battery positive electrode electrolyte: 1. The positive electrode electrolyte of the liquid flow battery is the electrolyte prepared in Example 6, the negative electrode electrolyte is a mixed solution of 1.5 M sodium tetrasulfide and 1 M sodium hydroxide, the diaphragm is Nafion, the positive electrode is blank carbon felt, and the negative electrode is carbon felt loaded with catalyst.

[0042] 2. Use the charge and discharge rate to perform performance test, and the discharge capacity diagram is as follows: Figure 5 As shown, the coulombic efficiency, energy efficiency and voltage efficiency are Figure 6 As shown, the performance test results are: at 80 mA / cm -2 The coulomb efficiency is 99.15%, the voltage efficiency is 73.27%, and the energy efficiency is 72.65%.

[0043] Comparative Example 1 A method for preparing a positive electrolyte for a liquid flow battery comprises the following steps: S1. Weigh 1 M equivalent of sodium hydroxide and dissolve it in water to form a mixed solution; S2. Weigh 2.3 M equivalent of ammonium ferrocyanide and lithium ferrocyanide mixed salt (molar ratio of 1:1) and place it in the mixed solution of step S1, and stir at 80° C. until dissolved to obtain a positive electrode electrolyte for a liquid flow battery.

[0044] The battery performance test was carried out on the prepared sulfur-iron liquid flow battery cathode electrolyte: 1. The positive electrode electrolyte of the liquid flow battery is the electrolyte prepared in Comparative Example 1, the negative electrode electrolyte is a mixed solution of 1.7 M sodium tetrasulfide and 1 M sodium hydroxide, the diaphragm is Nafion, the positive electrode is blank carbon felt, and the negative electrode is carbon felt loaded with a catalyst.

[0045] 2. The performance test is carried out using the charge and discharge rate. The coulomb and voltage efficiency diagrams at different current densities are as follows: Figure 3 As shown, the result is that at 80 mA / cm -2 The coulomb efficiency is 98.56%, the voltage efficiency is 55.65%, and the energy efficiency is 54.85%.

[0046] 3. Energy efficiency performance test under long-term constant current charging and discharging Figure 1 The stability test results are shown in Figure 2 As shown, at 80 mA / cm -2 After 300 consecutive cycles, the efficiency decayed, which shows that in the absence of additives, cyanide ions at high concentrations are very unstable, thus affecting the long cycle of the battery.

[0047] Comparative Example 2 A method for preparing a positive electrolyte for a liquid flow battery comprises the following steps: S1. Weigh 1 M equivalent of sodium hydroxide and dissolve it in water to form a mixed solution; S2, weighing 2.3 M equivalent of a mixed salt of ammonium ferrocyanide and lithium ferrocyanide (the molar ratio is 1:1) and placing it in the mixed solution of step S1, stirring at 80° C. until dissolved, to obtain a mixed salt solution; S3, weighing 10 mM equivalent of polyvinyl pyrrolidone, placing it in the mixed solution of step S2, stirring and dissolving, and obtaining a positive electrode electrolyte for a liquid flow battery; The battery performance test was carried out on the prepared sulfur-iron liquid flow battery cathode electrolyte: 1. The positive electrode electrolyte of the liquid flow battery is the electrolyte prepared in Comparative Example 2, the negative electrode electrolyte is a mixed solution of 1.7 M disodium tetrasulfide and 1 M sodium hydroxide, the diaphragm is Nafion, the positive electrode is blank carbon felt, and the negative electrode is carbon felt loaded with a catalyst.

[0048] 2. Use the charge and discharge rate to perform performance tests. The energy efficiency performance test under long-term constant current charge and discharge is shown in the figure below. Figure 1 As shown, at 80 mA / cm -2 The energy efficiency of long-term cycling at current density is shown in Figure 2. Figure 2 As shown, the coulomb and voltage efficiency diagrams at different current densities are shown in Figure 3 As shown, the test results are as follows: -2 The coulomb efficiency is 98.27%, the voltage efficiency is 58.76%, and the energy efficiency is 57.75%.

[0049] From the results of Comparative Example 2, it can be seen that the coulombic efficiency, voltage efficiency and energy efficiency have all dropped significantly, indicating that the failure to add a soluble Prussian blue derivative affects the charge transfer rate, thereby increasing the internal resistance and thus significantly reducing the energy efficiency.

[0050] Comparative Example 3 A method for preparing a positive electrolyte for a liquid flow battery comprises the following steps: S1. Weigh 1 M equivalent of sodium hydroxide and dissolve it in water to form a mixed solution; S2, weighing 2.3 M equivalent of a mixed salt of ammonium ferrocyanide and lithium ferrocyanide (the molar ratio is 1:1) and placing it in the mixed solution of step S1, stirring at 80° C. until dissolved, to obtain a mixed salt solution; S3. Weigh 10 mM equivalent of a soluble Prussian blue derivative (MnFe[Fe(CN)6xH2O]) and place it in the mixed solution of step S2, stir and dissolve to obtain a positive electrolyte for a liquid flow battery; perform a battery performance test on the prepared sulfur-iron liquid flow battery positive electrolyte.

[0051] 1. The positive electrode electrolyte of the liquid flow battery is the electrolyte prepared in Comparative Example 3, the negative electrode electrolyte is a mixed solution of 1.7 M sodium tetrasulfide and 1 M sodium hydroxide, the diaphragm is Nafion, the positive electrode is blank carbon felt, and the negative electrode is carbon felt loaded with a catalyst.

[0052] 2. Use the charge and discharge rate to perform performance tests. The energy efficiency performance test under long-term constant current charge and discharge is shown in the figure below. Figure 1 As shown, at 80 mA / cm -2 The energy efficiency of long-term cycling at current density is shown in Figure 2. Figure 2 As shown, the Coulomb and voltage efficiency diagrams at different current densities are shown in Figure 3As shown, the performance test results are: at 80 mA / cm -2 The coulomb efficiency is 98.56%, the voltage efficiency is 66.44%, and the energy efficiency is 65.55%.

[0053] It can be seen from the results of Comparative Example 3 that the coulombic efficiency, voltage efficiency and energy efficiency have all decreased significantly, indicating that the failure to add polyvinyl pyrrolidone leads to large-scale structural clustering of ions in the solution, which greatly affects the ionic conductivity of the electrolyte, thereby causing a decrease in energy efficiency.

[0054] Comparative Example 4 A method for preparing a positive electrolyte for a liquid flow battery comprises the following steps: S1. Weigh 1 M equivalent of sodium hydroxide and dissolve it in water to form a mixed solution; S2. Weigh 1.6 M equivalent of ammonium ferrocyanide and place it in the mixed solution of step S1, stir at 80°C until dissolved, and stir at 80°C until dissolved to obtain a positive electrolyte for a liquid flow battery; perform a battery performance test on the prepared iron-sulfur liquid flow battery positive electrolyte.

[0055] 1. The positive electrode electrolyte of the liquid flow battery is the electrolyte prepared in Comparative Example 4, the negative electrode electrolyte is a mixed solution of 1.2 M sodium tetrasulfide and 1 M sodium hydroxide, the diaphragm is Nafion, the positive electrode is blank carbon felt, and the negative electrode is carbon felt loaded with a catalyst.

[0056] 2. Use the charge and discharge rate to perform performance tests, such as coulomb efficiency, energy efficiency and voltage efficiency. Figure 6 As shown, the performance test results are: at 80 mA / cm -2 The coulomb efficiency is 98.16%, the voltage efficiency is 54.65%, and the energy efficiency is 53.65%.

[0057] Comparative Example 5 A method for preparing a positive electrolyte for a liquid flow battery comprises the following steps: S1. Weigh 1 M equivalent of sodium hydroxide and dissolve it in water to form a mixed solution; S2. Weigh 1.92 M equivalent of lithium ferrocyanide and place it in the mixed solution of step S1, stir at 80°C until dissolved, and stir at 80°C until dissolved to obtain a positive electrolyte for a liquid flow battery; perform a battery performance test on the prepared sulfur-iron liquid flow battery positive electrolyte.

[0058] 1. The positive electrode electrolyte of the liquid flow battery is the electrolyte prepared in Comparative Example 5, the negative electrode electrolyte is a mixed solution of 1.5 M sodium tetrasulfide and 1 M sodium hydroxide, the diaphragm is Nafion, the positive electrode is blank carbon felt, and the negative electrode is carbon felt loaded with a catalyst.

[0059] 2. The performance test was carried out using the charge and discharge rate. The performance test results showed that at 80 mA / cm -2 The coulomb efficiency is 98.32%, the voltage efficiency is 53.79%, and the energy efficiency is 52.89%.

[0060] From the comparison between Comparative Examples 4 and 5 and Examples 5 and 6, it can be seen that when the composite additive is 1:1, the single ferrocyanide can also play a role in improving the battery performance and long-term cycle stability.

Claims

1. A positive electrolyte for a liquid flow battery, characterized in that: The positive electrode electrolyte comprises the following components: ferrocyanide, a composite additive and a supporting electrolyte, wherein the molar ratio of the composite additive to the ferrocyanide is 0.1-5%; The composite additive comprises a soluble Prussian blue derivative and polyvinyl pyrrolidine.

2. The positive electrode electrolyte according to claim 1, characterized in that The ferrocyanide comprises two or more species, and the total concentration of the ferrocyanide is 1-3M.

3. The positive electrode electrolyte according to claim 2, characterized in that The ferrocyanide is composed of ammonium ferrocyanide and lithium ferrocyanide, and the molar ratio of ammonium ferrocyanide to lithium ferrocyanide is 1:10-10:

1.

4. The positive electrode electrolyte according to claim 1, characterized in that The amount ratio of the soluble Prussian blue derivative to the polyvinyl pyrrolidine substance is 1:3-3:

1.

5. The positive electrode electrolyte according to claim 1, characterized in that The supporting electrolyte includes sodium hydroxide and / or potassium hydroxide, and the concentration of the supporting electrolyte is 0.1-2M.

6. A method for preparing a positive electrolyte for a flow battery according to any one of claims 1 to 5, characterized in that: The following steps are involved: The supporting electrolyte, ferrocyanide and the composite additive are dissolved, stirred and mixed to form a mixed solution, wherein the concentration of the supporting electrolyte in the mixed solution is 0.1-2M.

7. The positive electrode electrolyte according to claim 6, characterized in that The ferrocyanide is dissolved at 50°C-80°C.

8. A liquid flow battery, characterized in that: The liquid flow battery is a sulfur-iron liquid flow battery, and the liquid flow battery comprises the liquid flow battery positive electrode electrolyte as described in any one of claims 1-5.

9. The flow battery according to claim 8, characterized in that The negative electrode electrolyte of the liquid flow battery is disodium tetrasulfide, the diaphragm is a cation exchange membrane, the positive electrode is blank carbon felt, and the negative electrode is carbon felt loaded with a catalyst.

10. The flow battery according to claim 9, characterized in that The flow battery is at 80 mA / cm -2 The energy efficiency reaches over 65% at a current density of 1.5 % and remains above 65% after 300 consecutive cycles.